Man-Machine-Environment System Engineering Proceedings of the 16th International Conference on MMESE - Long, Shengzhao; Dhillon, Balbir S. (Lecture Notes in Electrical Engineering, 2016)
This research topic was first established in China by Professor Shengzhao Long in 1981, with direct support from one of the greatest modern Chinese scientists, Xuesen Qian. In a letter to Shengzhao Long from October 22nd, 1993, Xuesen Qian wrote: "You have created a very important modern science subject and technology in China!" MMESE primarily focuses on the relationship between Man, Machine and Environment, studying the optimum combination of man-machine-environment systems. In this system, "Man" refers to working people as the subject in the workplace (e.g. operators, decision-makers); "Machine" is the general name for any object controlled by Man (including tools, machinery, computers, systems and technologies), and "Environment" describes the specific working conditions under which Man and Machine interact (e.g. temperature, noise, vibration, hazardous gases etc.). The three goals of optimization are to ensure "Safety, High efficiency and Economy" of man-machine-environment systems. These proceedings are an academic showcase of the best papers selected from more than 400 submissions, introducing readers to the top research topics and the latest developmental trends in the theory and application of MMESE. These proceedings are interdisciplinary studies on the concepts and methods of physiology, psychology, system engineering, computer science, environment science, management, education, and other related disciplines. Researchers and professionals who study an interdisciplinary subject crossing above disciplines or researchers on MMESE subject will be mainly benefited from these proceedings.